Susceptibility of Italian olive cultivars to various Colletotrichum species associated with fruit anthracnose. (6th October 2022) - Riolo, Mario; Pane, Antonella; Santilli, Elena; Moricca, Salvatore; Cacciola, Santa Olga
Abstract: Fruit anthracnose caused by Colletotrichum species is a major disease of olive ( Olea europaea ) worldwide. In this study, we tested in vitro the susceptibility of eight widely grown Italian olive cultivars and one Spanish cultivar to five Colletotrichum species. The Italian cultivars were Carolea, Cassanese, Coratina, Dolce Agogia, Frantoio, Leccino, Ottobratica and Sant'Agostino. The Spanish cultivar, included as a reference, was Picual. The five Colletotrichum species, included in pathogenicity tests, were C . acutatum, C . gloeosporioides, C . godetiae, C . karsti and C . nymphaeae . Olive drupes at comparable ripening stage were wound‐inoculated with a conidial suspension and the severity of infections was rated at various time intervals after inoculation using a scale of 0 to 6. The results were expressed in terms of relative area under disease progress curve (rAUDPC). C. acutatum was the most aggressive while C . karsti was the least aggressive among the Colletotrichum species tested. Frantoio and Leccino were the least susceptible cultivars while Ottobratica, Coratina and Carolea were the most susceptible to all Colletotrichum species. Separate experiments aimed to evaluate the effect of both inoculation method and drupe ripening stage on the interaction between Colletotrichum species and olive cultivars. Only C . acutatum and C . nymphaeae induced symptoms in nonwounded drupes. In general, the disease severity in green drupes was significantly lower than in mature drupes; however, the rankings of olive cultivars for their susceptibility to Colletotrichum species on both green and mature drupes showed similar trends. Abstract : Pathogenicity tests show a great variability in both the virulence of diverse Colletotrichum species associated with olive anthracnose and susceptibility of olive cultivars to infection by these species.